Landscapes of Mars - Vogt, Gregory L. (Springer, 2017)
Containing beautiful and exiting images that will spark the imagination, this is essentially a picture book providing a visual tour of Mars. All the major regions and topographical features are shown and supplemented with chapter introductions and extended captions. In a way, think of the book as a visual tourist guide. Other topics covered include Martian uplands, Giant volcanoes, the Grand Canyon of Mars, and much more. At the end of the book is an exciting gallery of the best 3D images of Mars making the book a perfect tool for understanding Mars and its place in the solar system.